(untitled) (Sciences & Technologie. C, Biotechnologies, 2007)
Algeria as all mediterranean countries is concert and endangered by regression of the forest and pastoral resources The forest of the Tlemcen Mountains are continually deteriorated and excessive pasture , the clearing and fires and endommaged the dynamic of the vegetation. This study is based on datas provided by exploitation of several hundered phyto-ecological “transcripts” realised in the Tlemcen region. The combination “use of two methods of analysis”: The ecological profiles method and “interspecific” relationships, wich is applicated in our transcripts permit to sketch the out lines of a strategy the conservation and development of the region in long term.